Physiological relevance, localization and substrate specificity of the alternative (type II) mitochondrial NADH dehydrogenases of Ogataea parapolymorpha - Juergens, Hannes; Mielgo-Gómez, Álvaro; Godoy-Hernández, Albert; ter Horst, Jolanda; Nijenhuis, Janine M.; McMillan, Duncan G. G.; Mans, Robert (Frontiers in Microbiology, 2024)
Mitochondria from Ogataea parapolymorpha harbor a branched electron-transport chain containing a proton-pumping Complex I NADH dehydrogenase and three Type II NADH dehydrogenases (NDH-2). To investigate the physiological role, localization and substrate specificity of these enzymes, the growth of various NADH dehydrogenase knockout mutants was quantitatively characterized in shake-flask and chemostat cultures, followed by oxygen-uptake experiments with isolated mitochondria. NAD(P)H:quinone oxidoreduction of the three NDH-2 were individually assessed. Our findings reveal that the O. parapolymorpha respiratory chain contains an internal NADH-accepting NDH-2 (Ndh2-1/OpNdi1), at least one external NAD(P)H-accepting enzyme, and likely additional mechanisms for respiration-linked oxidation of cytosolic NADH. Metabolic regulation appears to prevent competition between OpNdi1 and Complex I for mitochondrial NADH. With the exception of OpNdi1, the respiratory chain of O. parapolymorpha exhibits metabolic redundancy and tolerates deletion of multiple NADH-dehydrogenase genes without compromising fully respiratory metabolism.